Tea Farming Industry in Turkey and Social Economic History 1920-1960 - Rahşan İnal (Alternatif Politika, 2021)
This study aims to present the economic and social history of the tea farming industry in Turkey between 1920-1960. In Turkey, the “domestic tea” farming industry was initiated and continued under an initiative led by the nation-state at all stages. The present study investigates the historical process between 1920 and 1960 based on news reports from the central and local press, agricultural journals of the time, and parliamentary records, using also local, and regional historical resources. The state-led initiative is considered both an intervention that regulated social and economic structure in rural areas and a policy to encourage “domestic” tea consumption. The reasons underlying this intervention are addressed in two periods. In the first period, the primary goal was to overcome social and economic problems specific to Rize, the central city of tea cultivation, and the Eastern Black Sea Region, of which Rize is a part. In the second period of the state-led tea farming initiative, the goal was to complete the goals of the preceding period, and to satisfy the domestic demand for tea consumption through “national selfsufficiency” policies, and to start tea exports in the years to come. As a consequence of these efforts, not only tea has become a drink easily accessible by all social classes in Turkey today, but also the social structure in the tea-producing rural areas has been transformed.